Library Education in India at the Critical Cross Roads - Satija, M. P. (Journal of Information and Knowledge, 2007)
Traces the development of Library education in India. Identifies the reasons for the tardy growth of library education. Discusses the problems with the recruitment of librarians and LIS teachers. Suggests that syllabi should be according to the needs of the market.